Anal Phase Analysis of Thomas Hardy’s “Tess of The D’urbervilles” - Safnidar Siahaan (ANGLO-SAXON: Jurnal Ilmiah Program Studi Pendidikan Bahasa Inggris, 2017)
The research offers about the development phase analysis in Hardy’s novel “Tess of the D’Urbervilles”. This novel describes Tess as the victim of men who fall in love with her. Tess is one of Hardy's most sympathetic protagonists. She is as likeable as a literary character found in all of English literature. Throughout the novel, Hardy develops Tess as a character and describes her simple beauty. She is attractive to all men, and even her attempts to change her appearance are not enough to hide her natural beauty. Further in the story of the novel, Tess is depicted as a person of near divine qualities when she baptizes Sorrow before he dies. Hardy calls the effect on her siblings as a transfiguring effect" and that she looked with a touch of dignity which was almost regal. Tess' beauty is balanced by her earthy elegance, and this is especially evident when she is being courted by Angel at Talbothays. To know all of the protagonist’s characterization in this novel, the writer will analyze it based on the psychoanalysis theory focussing on the anal phase.  The result is expected to give the reader a better description and understanding of the Tess’ development phases.Keywords: anal phase, commencement, retentive, expulsion